172 Transforming the National Genomic Test Directory to Improve Genomic Testing for CNS Tumours - Jane Starczynski; Maricica Zabrautanu; Peter Street; Thomas Jacques; Kathreena Kurian; Ross Finnegan (Neuro-Oncology, 2026)
Abstract Introduction The National Genomic Test Directory (NGTD), introduced in 2019, defines NHS commissioned genomic tests in England and outlines their clinical eligibility. In cancers of the central nervous system (CNS), neuropathologists routinely integrate genomic analysis into diagnostic workflows to support tumour classification and clinical patient management. However, the existing Excel based NGTD is difficult to navigate and lacks the flexibility required, highlighting the need for a modernised, digital alternative. Methods The NHS England (NHSE) Genomics Unit undertook extensive stakeholder engagement to define the requirements for a digital directory. Test Directory content was evaluated alongside Patient Level Contract Monitoring data to identify requesting patterns, redundancy and evolving clinical needs. The WHO Blue Book on CNS Tumours was reviewed with adult and paediatric neuropathology experts to determine diagnostic genomic testing requirements, and relevant precision medicine genomic targets. The Digital Genomic Test Directory Service (DGTS) was developed as the platform to deliver the NGTD and support transformation of genomic testing for CNS tumours. Results Stakeholder input and data review demonstrated the need to update and restructure the NGTD in alignment with WHO classifications. A differential diagnostic approach was adopted, incorporating broader NGS panels that support integrated diagnosis while retaining targeted assays for urgent or salvage testing. Redundant tests identified through analysis were removed. Phase 1 of the programme has been completed, consolidating CNS tumour indications from 58 indications into seven streamlined test packages. Conclusions NHSE has initiated a major transformation to deliver the NGTD in a fully digital format via the DGTS, improving access to commissioned genomic tests essential for CNS tumour diagnosis and management. CNS tumours represent the first transformed disease area, setting the foundation for broader digital transformation across solid cancers.